Surgical Selection in Drug-Resistant Epilepsy: A Contemporary Evidence-Based Review of Patient Stratification, Presurgical Evaluation, and Surgical Outcomes - Vartika Gupta; Pankaj Gupta (Asian Journal of Neurosurgery, 2026)
Abstract Drug-resistant epilepsy (DRE) remains a major cause of neurological morbidity worldwide, affecting approximately one-third of patients with epilepsy despite advances in antiseizure medications. Persistent seizures are associated with increased mortality, cognitive decline, psychosocial impairment, and reduced quality of life. Surgical intervention represents the most effective treatment for carefully selected patients; however, substantial delays in referral and underutilization of epilepsy surgery continue to be reported globally. This study is done to provide a contemporary evidence-based review of patient selection, presurgical evaluation, surgical decision-making, and outcomes across the spectrum of epilepsy surgery modalities. A narrative review of the current literature was performed, focusing on the definition of DRE, indications for surgical referral, presurgical investigations, resective and disconnective surgical procedures, minimally invasive techniques, and neuromodulation strategies. Emphasis was placed on practical clinical decision-making and contemporary developments influencing patient selection. Successful epilepsy surgery depends primarily on accurate localization of the epileptogenic zone and careful multidisciplinary evaluation. Temporal lobe epilepsy remains the most favorable indication for resective surgery, while advances in stereoelectroencephalography, neuroimaging, laser interstitial thermal therapy, and neuromodulation have expanded treatment options for patients previously considered unsuitable for surgery. Contemporary presurgical assessment integrates clinical semiology, prolonged video-electroencephalographic monitoring, high-resolution magnetic resonance imaging, functional imaging, and neuropsychological evaluation to optimize patient selection and maximize postoperative seizure control. Appropriate patient selection remains the cornerstone of successful epilepsy surgery. Continued advances in imaging, electrophysiology, minimally invasive techniques, and neuromodulation are transforming the management of DRE and facilitating increasingly individualized treatment strategies.